DFT, QTAIM and NBO Investigation of the Interaction of Rare Gases with Pristine and Decorated Boron Nitride Nanotube. Issue 34 (11th September 2018) - Nemati‐Kande, Ebrahim; Abbasi, Mahdi; Doust Mohammadi, Mohsen
Abstract: In this work, the interactions of pristine, Al‐ and Ga‐doped single walled armchair (5, 5) boron nitride nanotubes (BNNTs) with He, Ne, Ar and Kr rare gases (RGs) were fully investigated using several different density functional theory (DFT) functionals including pure‐GGA (PBEPBE), hybrid‐GGA (B3LYP), meta‐hybrid‐GGA (M062X) and long‐range‐corrected B3LYP (CAM−B3LYP) in combination with two 6–31G(d) and 6–311+G(d) basis sets. Natural bond orbital (NBO) and quantum theory of atoms in molecule (QTAIM) analyses were also performed to better understand the intermolecular interaction between RGs and nanotubes. The adsorption energies ( E ads ) indicate that RGs could be adsorbed on the surface of the BNNTs with the following trend: Ne > Kr > Ar > He. The E ads energies obtained using CAM−B3LYP method have also been found to be 13–18%, (for Ne−Kr) and 32–44% (for He−Ar) higher than those obtained from normal B3LYP functional. Moreover, analysis of the natural partial charges reveals the small charge transfer from RGs to BNNTs, which confirms the sensing of RGs by BNNTs. QTAIM analysis also supports the existence of close‐shell (non‐covalent) interactions between BNNTs and RGs. Generally, according to the obtained results, it can be concluded that, Al‐ and Ga‐doped BNNTs are remarkably more sensitive to RGs than pristine‐BNNT, and may be good candidates in designing new RG sensors. Abstract : The adsorption of He, Ne, Ar and Kr rare gases (RGs) onto the outer surface of pristine, Al‐ and Ga‐doped single wall boron nitride nanotubes were investigated theoretically using several DFT methods. NBO and QTAIM analyses confirmed the physical adsorption of rare gases onto the surface of nanotubes via van der Waals interactions. It was found that, Al‐ and Ga‐doped nanotubes are promising materials for designing new RG sensors.